Transcatheter aortic valve implantation with commissural alignment - D. V. Salichkin; A. E. Komlev; P. M. Lepilin; A. S. Kolegaev; I. V. Kuchin; A. A. Nurkhametova; T. E. Imaev (Евразийский Кардиологический Журнал, 2023)
Transcatheter aortic valve implantation (TAVI) is commonly accepted method of treatment of aortic stenosis in most patients with currently increasing number of TAVI procedures. Patients after TAVI frequently have indications for percutaneous coronary intervention (PCI) that might be technically challenging due to the presence of transcatheter valve. Compromising coronary ostia involves such issues as design of the prosthesis and its position in the aortic root with respect to the commissures of native aortic valve. Since TAVI with commissural alignment can mitigate risk of compromising coronary ostia, this option should be considered while planning TAVI, especially in younger patients with coronary atherosclerosis and relatively high probability of PCI in the future. The algorithm of commissural alignment in clinical practice of TAVI up to date has been proposed only for several transcatheter heart valves reported in this paper.